3X+24-2X=9+4X-6

Simple and best practice solution for 3X+24-2X=9+4X-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3X+24-2X=9+4X-6 equation:


Simplifying
3X + 24 + -2X = 9 + 4X + -6

Reorder the terms:
24 + 3X + -2X = 9 + 4X + -6

Combine like terms: 3X + -2X = 1X
24 + 1X = 9 + 4X + -6

Reorder the terms:
24 + 1X = 9 + -6 + 4X

Combine like terms: 9 + -6 = 3
24 + 1X = 3 + 4X

Solving
24 + 1X = 3 + 4X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-4X' to each side of the equation.
24 + 1X + -4X = 3 + 4X + -4X

Combine like terms: 1X + -4X = -3X
24 + -3X = 3 + 4X + -4X

Combine like terms: 4X + -4X = 0
24 + -3X = 3 + 0
24 + -3X = 3

Add '-24' to each side of the equation.
24 + -24 + -3X = 3 + -24

Combine like terms: 24 + -24 = 0
0 + -3X = 3 + -24
-3X = 3 + -24

Combine like terms: 3 + -24 = -21
-3X = -21

Divide each side by '-3'.
X = 7

Simplifying
X = 7

See similar equations:

| (3a-4b)(8a-5b)= | | 736926836816837816383681728.738285375271638362736728h=581.7h*6376.24 | | 4X-6X+22=3X+27 | | h=5817h*6376 | | h=0h*6376 | | 5.4=1.3x+1.5 | | h=1h*6376 | | 4y-28=-49+7y | | h=1h | | 4b+26=50 | | 7n-3=27+2n | | 3=.2x-7 | | (56)34g*4568284792638718462677488=537g*34 | | -(3x+4)=x-16 | | 5x-6y=64 | | 160+80+x=180 | | 7+2x=2(x-1)+4 | | 5x-12=-2+5(x-2) | | 24x+36x+108x= | | 7387178g*71893=g/783878278672614460 | | 8x+4=9+4(2x-1) | | -7e-3= | | 8y-3=20y+93 | | 2s^2+7s+6=0 | | 13*2-10= | | [4-(-49)]= | | 2x-(180-x)=27 | | 168.2=i^2(20) | | y(5y)=2000 | | 3t+19=-10 | | 10x-4=4x+1 | | 2t^8(t-t+7t^3)= |

Equations solver categories